Formulasi Yogurt Sari Buah Belimbing Wuluh (Averrhoa bilimbi L.) Dan Pengaruhnya Terhadap Penurunan Kadar Glukosa Darah Mencit (Mus musculus) - Rahmayanti, Rahmayanti; Mursyid, Murni; Astari, Chitra (Program Studi Farmasi Universitas Mandala Waluya, 2024)
Indonesia is a country that ranks 5th out of 10 countries with the highest number of diabetics in the world. One of the plants that can be used as an antidiabetic is the fruit of belimbing wuluh (Averrhoa bilimbi L.). This study aims to determine the physical quality of wuluh star fruit juice yogurt and determine at what concentration wuluh star fruit juice yogurt can affect blood sugar levels of mice (Mus musculus). Mice as test animals were induced glucose and compared its effectiveness with acarbose. In this study, 5 treatment groups were used, namely giving yogurt without juice (negative control), acarbose (positive control), 0.35 ml star fruit juice yogurt, 0.50 ml star fruit juice yogurt, and 0.65 ml star fruit juice yogurt. Blood glucose measurement was done for 3 days. The results showed that star fruit juice can be formulated in the form of yogurt, and meet the standards of good physical stability, namely organoleptic test, pH, and viscosity. In the antidiabetic test, the results showed that all concentrations could affect the blood sugar levels of mice, with a decrease of 90 mg/dl at a concentration of 0.35 ml, a decrease of 92 mg/dl at a concentration of 0.50 ml, and a decrease of 100 mg/dL at a concentration of 0.65 ml. It was concluded that the most effective concentration to affect the blood sugar levels of mice was a concentration of 0.65 ml with a decrease of 100 mg/dl.